Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13287-015-0247-2
|View full text |Cite
|
Sign up to set email alerts
|

Regionally-derived cell populations and skeletal stem cells from human foetal femora exhibit specific osteochondral and multi-lineage differentiation capacity in vitro and ex vivo

Abstract: BackgroundAdult skeletal stem cells (SSCs) often exhibit limited in vitro expansion with undesirable phenotypic changes and loss of differentiation capacity. Foetal tissues offer an alternative cell source, providing SSCs which exhibit desirable differentiation capacity over prolonged periods, ideal for extensive in vitro and ex vivo investigation of fundamental bone biology and skeletal development.MethodsWe have examined the derivation of distinct cell populations from human foetal femora. Regionally isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…These results are in agreement with previous reports. In [ 10 ], the percentage of Stro-1 + cells in adult human BM cells declined to 8.5% after six weeks in culture, and in [ 22 ], Stro-1 + cells were completely absent at passage 7, after 21–35 DIV, in human fetal femur-derived BM cell cultures. Stewart et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with previous reports. In [ 10 ], the percentage of Stro-1 + cells in adult human BM cells declined to 8.5% after six weeks in culture, and in [ 22 ], Stro-1 + cells were completely absent at passage 7, after 21–35 DIV, in human fetal femur-derived BM cell cultures. Stewart et al .…”
Section: Resultsmentioning
confidence: 99%
“…ALP activity was quantified against a standard curve (p-nitrophenol) by incubation of the cell lysate with a phosphatase substrate solution (1.33 mg ml −1 p -nitrophenyl phosphate in 0.5 M alkaline buffer solution) at 37°C in the dark, under gentle agitation. The reaction was terminated by addition of 1 M NaOH in dH 2 O after 40 min and absorbance was measured at 410 nm using an ELx800™ absorbance reader (BioTek) [ 22 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…These alloys also promote the osteogenic differentiation of hAMSCs (Marini et al, ). In addition, a recent study by Gothard et al () has shown that regionally derived cell populations and skeletal stem cells from human fetal femora exhibit specific osteochondral and multi‐lineage differentiation capacity both ex vivo and in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a direct comparison of fetal chondroprogenitors from different origins, such as femoral head, spine and ulnar epiphysis (used in this study), could determine the most stable cell source for cartilage regeneration. Reports by others suggest that cells isolated from fetal femoral head progress towards hypertrophic cartilage in vitro (Quintin et al , ; Gothard et al , ).…”
Section: Discussionmentioning
confidence: 99%